Biblical Touch in Wages - Budianto Tedjasuksmana (International Journal of Religious and Cultural Studies, 2022)
This article discloses the church's social teaching that denounces capitalist thinking, because workers are seen only as labourers. Workers who work only by relying on the spirit of love could accept their life situations patiently and steadfastly. Work has a place of honor in the sight of God. By exploring biblical texts the concept of wage was analysed. This research was conducted through participative observation and interviews by employing the classical phenomenology as well as the hermeneutic approach, while non-empirical data collection method was done by interpreting biblical text based on theologians. Workers, especially Christians, generally believe in doing their work based on the principle of obedience. This attitude reflects the value of the teachings of faith. Giving oneself through service in work can be seen as a calling in carrying out the mission of the Church has become an alternative meaning of wages.